D-ribose-mediated glycation of fibrinogen: Role in the induction of adaptive immune response. (1st November 2022) - Alouffi, Sultan; Khanam, Afreen; Husain, Arbab; Akasha, Rihab; Rabbani, Gulam; Ahmad, Saheem
Abstract: A nonenzymatic reaction between reducing sugars and amino groups of proteins results in the formation of advanced glycation end products, which are linked to a number of chronic progressive diseases with macro- and microvascular complications. In this research, we sought to ascertain the immunological response to d -ibose-glycated fibrinogen. New Zealand White female rabbits were immunized with native and d -ribose-glycated (Rb-gly-Fb) fibrinogen and used for studying the immunological response. Serum from these rabbits analyzed using direct binding and competitive inhibition ELISA was found to contain a high titer of antibodies against Rb-gly-Fb; Rb-gly-Fb was much more immunogenic than its native form. The IgG against Rb-gly-Fb (Rb-gly-Fb-IgG) was highly specific against the immunogenic protein. Moreover, histopathology and immunofluorescence studies revealed the deposition of the Rb-gly-Fb-IgG immune complex in the glomerular basement membrane of the kidneys of immunized rabbits. Furthermore, immunization with Rb-gly-Fb increased the expression of genes encoding proinflammatory cytokines, tumour necrosis factor α, interleukin-6, interleukin-1β, and interferon-gamma, which is indicative of increased inflammation and the antigenic role of Rb-gly-Fb in provoking an immune response. Highlights: Fibrinogen because of glycation results in the structural perturbations. Fibrinogen protein becomes highly immunogenic after the glycation reaction. Immunogenicity of the Fibrinogen is due to the formation of neo-epitopes in its structure.